Changes in prevalence of periodontitis in two German population‐based studies. (10th February 2015) - Schützhold, Svenja; Kocher, Thomas; Biffar, Reiner; Hoffmann, Thomas; Schmidt, Carsten O.; Micheelis, Wolfgang; Jordan, Rainer; Holtfreter, Birte
Abstract Aim We aimed to assess changes of periodontal status in Germany. Materials & Methods The Studies of Health in Pomerania (SHIP) are two cross‐sectional population‐based studies conducted during 1997–2001 (SHIP‐0, 20–81 years, n = 3736) and 2008–2012 (SHIP‐Trend, 20–84 years, n = 3622) in northeast Germany. The German Oral Health Studies (DMS, 35–44 and 65–74 years) are national cross‐sectional population‐based surveys conducted in 1997 (DMS III, n = 1454) and 2005 (DMS IV, n = 1668), whose results were separately reported for West and East Germany. Prevalences, percentages and numbers of teeth affected were defined. Results In SHIP, prevalence of attachment loss (AL) ≥3 mm decreased from 89.7% (95% confidence interval (CI): 88.6–90.8) to 85.1% (95%CI: 83.9–86.3) (p < 0.05) and the mean extent reduced from 62.8% (95%CI: 61.7–63.8) to 55.9% (95%CI: 54.9–56.9) (p < 0.05). Probing depth (PD) ≥4 mm and the respective extent remained unchanged. In West Germany, AL ≥3 mm decreased for 35–44‐year‐olds and increased for 65–74‐year‐olds (p < 0.05). In SHIP and DMS, the number of teeth in dentates increased significantly in all age groups. Conclusions Prevalences and extents of AL improved almost in all age categories in SHIP and West German adults, whereas PDs remained unchanged. Nonetheless, the improvement of periodontal conditions implies an increase of treatment needs regarding moderately diseased teeth because of simultaneous increases of the number of present teeth.